2018
DOI: 10.5334/jbsr.1386
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of Metaplastic Carcinoma of the Breast with Pathologic Correlation

Abstract: Objectives:To review the imaging findings of a series of cases of metaplastic carcinoma of the breast, a rare and aggressive form of breast cancer with variable imaging features.Materials and methods:Retrospective review of multimodality imaging features of eleven cases of metaplastic carcinoma of the breast retrieved from a single hospital institution database. Clinical and pathologic data were also documented.Results:The median age of presentation was 65 years. Four cases had axillary lymphadenopathies, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 19 publications
7
38
1
Order By: Relevance
“…In the present study, six patients with MBC (54.5%) had tumors with an oval shape on imaging, and four patients with MBC (36.4%) had tumors with ill-defined margins on imaging, which is similar to a previously published study [15]. Donato et al reported that in MBC, an oval dense mass with a non-circumscribed margin was most common on imaging [14]. Petterson et al reported the imaging findings on mammography in nine patients and showed that cases of MBC that had an irregular or spiculated margin had an IDC component of metaplastic carcinoma [4].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, six patients with MBC (54.5%) had tumors with an oval shape on imaging, and four patients with MBC (36.4%) had tumors with ill-defined margins on imaging, which is similar to a previously published study [15]. Donato et al reported that in MBC, an oval dense mass with a non-circumscribed margin was most common on imaging [14]. Petterson et al reported the imaging findings on mammography in nine patients and showed that cases of MBC that had an irregular or spiculated margin had an IDC component of metaplastic carcinoma [4].…”
Section: Discussionsupporting
confidence: 89%
“…Pezzi et al compared the biological behavior of 892 patients with MBC with 255,164 patients with invasive ductal carcinoma (IDC) and reported that 5.5% of patients with MBC had a tumor size of less than 10 mm, compared with 26.9% of patients IDC [13]. Donato et al reported that the median tumor size in cases of IDC was 27 mm [14]. In the present study, the mean diameter of the tumor was 3.43 cm on mammography, which is similar to the findings in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several other studies on MBC have reported similar age incidences, because these women tend to be older than 50 years. 2,14,20,21 An intriguing finding from our study was the fact that these tumors can indeed grow to be very large, confirming prior observations that they tend to grow larger than ductal carcinomas. 14,16,22 We observed a maximum tumor size of 21.5 cm from our cohort of patients.…”
Section: Treatment and Outcomesupporting
confidence: 89%
“…Early diagnosis presents a challenge, as the radiologic phenotypes of MBC are diverse and may mimic benign lesions or other invasive breast carcinomas. There is no mammographic or sonographic appearance that reliably predicts the presence of MBC [3][4]. High signal intensity on T2-weighted magnetic resonance imaging (MRI) related to the necrotic component of the 1 2 3 1 4 tumor, however, may be a useful imaging marker [5].…”
Section: Introductionmentioning
confidence: 99%